The Effectiveness of Using Authentic Englsih Youtube Media in Improving Students’ Oral Reading - Irma Zuraini; Asnawi Muslem; Nurul Inayah (Universitas Syiah Kuala, 2021)
This study aimed at finding out whether using YouTube media can sigficantly improve students’ oral reading in three aspects; rate, fluency, and accuracy. A pre-experimental study with one group pretest-posttest design was undertaken by giving the students oral reading test. The sample of this study was 19 students of VIII-1 class of SMP 14 Banda Aceh. The result showed that the students’ oral reading scores were significantly improved from 46.93 in the pre test to 71.45 in the post test. The findings of this study revealed that t-test value was 17,832, while the t-table value was 2.120. It means the t-table value was lower than the t-test value (ts=17,832tt= 2.120). In conclusion, there was a significant improvement on students’ oral reading ability after they were taught by using YouTube. The result, thus, explains that Youtube can also be useful in improving oral reading in EFL classrooms.